2013
DOI: 10.1007/s11033-013-2619-y
|View full text |Cite
|
Sign up to set email alerts
|

The molecular phylogenetic signature of Bali cattle revealed by maternal and paternal markers

Abstract: Bali cattle is a domestic cattle breed that can be found in Malaysia. It is a domestic cattle that was purely derived from a domestication event in Banteng (Bos javanicus) around 3,500 BC in Indonesia. This research was conducted to portray the phylogenetic relationships of the Bali cattle with other cattle species in Malaysia based on maternal and paternal lineage. We analyzed the cytochrome c oxidase I (COI) mitochondrial gene and SRY of Y chromosome obtained from five species of the Bos genus (B. javanicus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
1
15
0
1
Order By: Relevance
“…DNA was extracted from these samples using QIAGEN QIAamp DNA Micro Kit and amplified with Polymerase Chain Reactions (PCRs) using an Eppendorf Mastercycler. One pair of specific primers were used to amplify the D-loop region: Walid F (TCA CCG TCA ACT CCC AAA GCT GA) and Walid R (AGG GGG AAG TTT TAT GGA AGG GGG) (Syed-Shabthar et al 2013). PCR components used in this study were Taq DNA polymerase (5 U/µL), 10X PCR Buffer, 50 mM MgCl 2 and 10 mM dNTP.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA was extracted from these samples using QIAGEN QIAamp DNA Micro Kit and amplified with Polymerase Chain Reactions (PCRs) using an Eppendorf Mastercycler. One pair of specific primers were used to amplify the D-loop region: Walid F (TCA CCG TCA ACT CCC AAA GCT GA) and Walid R (AGG GGG AAG TTT TAT GGA AGG GGG) (Syed-Shabthar et al 2013). PCR components used in this study were Taq DNA polymerase (5 U/µL), 10X PCR Buffer, 50 mM MgCl 2 and 10 mM dNTP.…”
Section: Methodsmentioning
confidence: 99%
“…All the phylogenetic tree topologies showed a significant separation between the outgroup (bison and water buffalo) and the ingroup (Malayan gaur). The outgroup was selected based on previous studies that also used the Bos genus in their studies (Rosli et al 2011(Rosli et al , 2016Syed-Shabthar et al 2013). For the NJ tree, clade A was formed by the separation of bison from Malayan gaur, supported with a 100% bootstrap value.…”
Section: Nj and Mp Tree Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Some research reports using DNA barcode on birds (Herbert et al 2004), Indonesian local cattle (Febriana 2011), chicken (Gao et al 2011), cetartiodactyla (Zein & Fitri 2012), bali cattle (Syed-Shabthar et al 2013) and Indonesian local buffalo (Saputra et al 2013) has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, fecal samples are important in studies that require DNA sources from risky or highly endangered subjects before samples are collected in the wild [4, 9]. With several nonconventional DNA extraction kits and enhanced PCR chemicals available today, DNA analysis of fecal sources is no longer impossible [10]. In this study, we focused on extracting DNA from fecal samples that are believed to be otter feces, collected from several regions, to identify species.…”
Section: Introductionmentioning
confidence: 99%